Handheld Echocardiography: Current State and Future Perspectives. Issue 22 (28th November 2017) - Chamsi-Pasha, Mohammed A.; Sengupta, Partho P.; Zoghbi, William A.
Abstract : Echocardiography is the primary imaging modality for diagnosing cardiac conditions. Over the past 2 decades, technological advancements have resulted in the emergence of miniaturized handheld ultrasound equipment that is compact and battery operated, and handheld echocardiography can be readily performed at the point of care with reasonable image quality. The simplicity of use, availability at the patient's bedside, easy transportability, and relatively low cost have encouraged physicians to use these devices for prompt medical decision making. As a consequence, the use of handheld echocardiography is on the rise even among nonechocardiographers (intensivists, emergency care physicians, internists, and medical students). One of the real utilities of ultrasound-augmented clinical diagnosis is in evaluating patients efficiently and selecting patients for appropriate downstream diagnostic testing including comprehensive echocardiography. Although clinical evidence supports the use of handheld devices in various clinical settings and by different users, proficiency in point-of-care ultrasound requires dedicated training in both performance and interpretation. This review summarizes the existing literature on the use of handheld echocardiography in conducting focused cardiac examinations: its training requirements, challenges, opportunities, and future perspectives in the care of the cardiovascular patient.